Continuous glucose monitoring in critically ill adult patients: results of a pilot study in Greece - Myrou, Athena D.; Didaggelos, Triantafyllos P.; Geka, Hellen G.; Pertsas, Evangellos M.; Ginas, Dimitrios K.; Didaggelos, Matthaios B.; Aslanidis, Theodoros K.; Barmpagiannos, Konstantinos G.; Theodoridis, Andreas I.; Spanou, Styliani A.; Kotzakioulafi, Evelina E.; Savopoulos, Christos G. (International Journal of Research in Medical Sciences, 2024)
Background: Continuous glucose monitoring has emerged as a promising tool in managing glycemic control for patients with type 2 diabetes admitted to the intensive care unit. This paper provides a comprehensive review of the potential benefits, challenges, and implications associated with continuous glucose monitoring utilization in intensive care unit settings for type 2 diabetic patients. Methods: In a prospective observational study continuous glucose monitoring systems were applied in adult intensive care unit patients in two centers. Eighty patients were randomly assigned into 2 groups: one with continuous glucose monitoring system one with standard glucose monitoring, previous medical history, reason for intensive care unit admission, demographic characteristics and laboratory parameters were recorded. Results: Recordings from six patients were excluded from analysis. Patients on home insulin and tablet combination therapy had worse glycemic control than subjects on insulin monotherapy or oral tablets alone. There was no difference in the glycemic profile of patients before and within the unit between those who were Covid-19 positive and those who had different reasons for admission to the unit. However, obese subjects had significantly worse glycemic control. Glucose measurements with continuous glucose monitoring and standard method were in almost total agreement. Conclusions: While continuous glucose monitoring benefits may allow a more personalized therapeutic strategy, further research is necessary to evaluate the cost-effectiveness and long-term implications of continuous glucose monitoring implementation in the intensive care unit setting.